Bugs and Society I : Raising Awareness About Endemic Biodiversity - Arroz, Ana Margarida Moura (2018)
The negative impact of biodiversity loss on ecosystem functioning and services, and ultimately on human well-being, has been unequivocally established; however, despite all efforts, biodiversity is still declining worldwide. It is widely accepted that biodiversity awareness is crucial for its conservation. Nevertheless, after many initiatives to alert society about the consequences of losing biodiversity, biodiversity loss is still perceived as a minor environmental risk compared to others such as climate change. Thus far, most communication strategies have involved conventional venues, targeting people who are already “environmentally-aware”, and have not incorporated societal idiosyncrasies and cultural backgrounds. The wicked problem of loss of biodiversity and the existing strategies to promote people’s engagement are discussed under the risk communication framework. The risk perspective focuses science communication on the mitigation of risk and/or the minimisation of its consequences. Further, it helps to keep the target in mind, to establish activities and strategies that are useful for reaching the proposed goals, and to regulate the processes based on desired outcomes. After presenting the role of communication in risk governance, the principles and strategic options of the Azorean intervention, Bugs & Society, are presented. This communicational programme will be analysed and evaluated in another chapter through the presentation of two activities, which are provided as examples for further discussion.